The Influence of Social Factors on Consumer Buying Behaviour of Female Sanitary Ware in Gwarinpa District of Abuja, Nigeria - Marcus Garvey Orji; Akhimien Emmanuel; Daramola Ebunoluwa Ayishatu (Britain International for Academic Research (BIAR) Publisher, 2023)
No matter the type of products that are introduced into a market, there has to be analysis of the target market and how consumers will react to those products. Anyone going into a venture or starting a business must have knowledge on consumer buying behaviour, while this does not guarantee sales; it gives entrepreneurs and marketers insight on how to understand the buying behaviour of consumers. The main objective of this study was to assess the influence of social factors on consumer buying behaviour of female sanitary ware in Gwarinpa District of Abuja, with particular emphasis on Molped Sanitary ware. The study is a survey research sampling the opinion of three hundred and twenty three women in the District. Their opinions were collected using a structured questionnaire. The data collected were analysed by tabulations, percentages and formulated hypotheses tested using Kendall coefficient of concordance. The findings reveal that family plays a significant role in influencing consumer buying behaviour of Molped female sanitary ware in Gwarinpa District of Abuja; also reference groups, role and status influences consumer buying behaviour of female sanitary ware in the District. The study concluded that social factors are significantly relevant in influencing consumer buying behaviour of female sanitary ware in Gwarinpa District of Abuja. And therefore recommended amongst others that family members should learn about the most comfortable and environmentally friendly sanitary wares they purchase in order to set an exemplary role for the younger ones; equally friends and colleagues should encourage each other and promote awareness on good sanitary wares available to them like Molped products to promote good hygiene among young women.